Vape shops: who uses them and what do they do? - Pattinson, Julie; Lewis, Sarah; Bains, Manpreet; Britton, John; Langley, Tessa (BioMed Central, 2018)
Background: ‘Vape shops’ are a popular source for buying electronic cigarettes (e-cigarettes) and related products. The products that vape shops sell, their marketing techniques and the extent to which they provide information or encouragement to smokers to quit tobacco use, as well as the patterns of tobacco and e-cigarette use of their customers are not well understood. Methods: We conducted cross-sectional surveys in vape shops in the East Midlands region of the United Kingdom, one with shop staff (n=41), and one with customers (n=197). Results: The majority of customers (84%) currently used e-cigarettes. Among current vapers, 19% were dual users and 78% had quit smoking. Over half of vapers reported using a lower level of nicotine in their current e-liquid than when they started using e-cigarettes. There was a wide variety in products and price ranges between the shops. Many staff reported that customers ask for information about quitting smoking (90%). Less than half reported providing smoking cessation advice, although 76% of staff reported feeling confident about delivering cessation advice to customers who ask for it. Just under half of customers and shop staff said they thought it was appropriate to deliver formal in-19 store smoking cessation support. Conclusions: The majority of vape shop customers are vapers who have quit smoking. Shop staff play a central role in providing customers with product information, and many provide smoking cessation advice. Further research is needed to investigate the potential for smoking cessation interventions in vape shops, including the extent to which these would appeal to non-vapers.